Young Stellar Object Jets Magnetocentrifugally Driven by Reconnecting Atmospheric Avalanche Accretion Streams above Inner Circumstellar Disks - Yisheng Tu; Zhi-Yun Li; Zhaohuan Zhu; Xiao Hu; Chun-Yen Hsu (The Astrophysical Journal)
Fast, collimated jets are ubiquitous features of young stellar objects. They are generally thought to be powered by disk accretion, but the details are debated. Through 2D (axisymmetric) MHD simulations, we find that a fast (>100 km s ^−1 ) collimated bipolar jet is continuously driven along the north and south poles of a circumstellar disk that is initially magnetized by a large-scale open poloidal field and contains a thermally ionized inner magnetically active zone surrounded by a dead zone. The fast jet is primarily driven magnetocentrifugally by the release of the gravitational binding energy of the so-called “avalanche accretion streams” near the boundary of an evacuated poloidal field dominated polar region and a thick disk atmosphere raised by a toroidal magnetic field. Specifically, the fast outflow is driven along the upper (open) branch of the highly pinched poloidal field lines threading the (strongly magnetically braked) accretion streams, where the density is relatively low so that the lightly loaded material can be accelerated magnetocentrifugally along the open field line to a high speed. The highly pinched poloidal magnetic fields threading the avalanche accretion streams tend to reconnect, enabling mass to accrete to the center without dragging along the poloidal magnetic flux with it. The reconnection provides a potential heating source for producing chondrules and calcium- and aluminum-rich inclusions.